Diversity and Antimicrobial Potential of Cultivable Endophytic Actinobacteria Associated With the Medicinal Plant Thymus roseus - Musa, Zulpiya; Ma, Jinbiao; Egamberdieva, Dilfuza; Abdelshafy Mohamad, Osama Abdalla; Abaydulla, Gulsumay; Liu, Yonghong; Li, Wen-Jun; Li, Li (Frontiers in Microbiology, 2020)
We report for the first time the isolation of endophytic actinobacteria associated with wild populations of the Chinese medicinal herb Thymus roseus Schipcz obtained from the arid land in Ili and Tacheng of the Xinjiang Province, China. Strains were isolated by special pretreatment of plant tissues and identified based on their 16S rRNA gene sequences, and their antimicrobial activities in vitro were evaluated. A total of 126 endophytic actinobacteria belonging to two classes, eight orders, 14 families, and 24 genera were isolated from different organs at the Ili and Tacheng sites. In addition, the diversity of culturable endophytic actinobacteria genera was higher at Tacheng site (n = 71, 56.35%) than the Ili site (n = 55, 43.65%). A neighbor-joining tree of 126 isolated actinobacteria showing the phylogenetic relationships based on 16S rRNA gene sequences and the genus Streptomyces was the most dominant isolate. The number of endophytic actinobacteria genera obtained from root tissues (n = 54, 42.86%) was higher compared to stem (n = 35, 27.78%) and leaf tissue (n = 37, 29.36%). Among 126 endophytic actinobacteria, 54 strains were antagonistic against at least one or more indicator organisms in vitro. Notably, most strains of Streptomyces proved antagonistic activities. For example, strain T4SB028, namely Streptomyces polyantibioticus, showed the highest inhibition ratio reached 67.06, 64.20, and 70.55% against Alternaria solani, Valsa malicola, and Valsa mali, respectively. The results demonstrate that about 30.95%, 23.01% of the tested endophytic actinobacteria were capable of producing siderophores and chitinase, respectively. Additionally, the results of the amplification of biosynthetic genes polyketide synthetase (PKS-I) and non-ribosomal peptide synthetase (NRPS) indicated that at least one antibiotic biosynthetic gene was detected in 27 (50%) of the tested strains. Our result emphasizes that the endophytic actinobacteria communities are different based on the plant tissues and the geographical environment of the sampled area. Thus, we conclude that T. roseus Schipcz. provided a rich source of endophytic actinobacteria that exhibited a broad-spectrum antimicrobial agent.